2001
DOI: 10.1080/09064700119540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fibre on Digestibility and Energy Metabolism in Pregnant Sows

Abstract: This study was undertaken to provide information on the effect of two levels of dietary bre (DF) [184 vs. 407 g DF kg ¼ 1 dry matter (DM)] on the digestibility of nutrients and energy metabolism in pregnant sows during different stages of pregnancy. The amount of DF in the high-bre diet was supplied by dried sugar beet pulp (20%) and oats, wheat bran and grass pellets. The intake of metabolizable energy (ME) was similar for both the low-bre and the highbre diet, with an average daily intake of 30.74 MJ. Digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…In connection with the absence of effect of diet composition on main components of HP, total HP was not affected by the addition of DF in the diet. This result contrasts with previous studies, which showed an increased heat increment with the DF level in growing pigs (Jørgensen et al 1996) or in adult sows (Noblet et al 1993a;Ramonet et al 2000;Olesen et al 2001). In fact, the variation of DF level between the control and the DF-rich diet was low (90 g DF/kg DM) when compared with those of the latter studies (approximately 200 g DF/kg DM).…”
Section: Dietary Fibre and Metabolic Energy Utilisation Of Diets In Acontrasting
confidence: 77%
See 2 more Smart Citations
“…In connection with the absence of effect of diet composition on main components of HP, total HP was not affected by the addition of DF in the diet. This result contrasts with previous studies, which showed an increased heat increment with the DF level in growing pigs (Jørgensen et al 1996) or in adult sows (Noblet et al 1993a;Ramonet et al 2000;Olesen et al 2001). In fact, the variation of DF level between the control and the DF-rich diet was low (90 g DF/kg DM) when compared with those of the latter studies (approximately 200 g DF/kg DM).…”
Section: Dietary Fibre and Metabolic Energy Utilisation Of Diets In Acontrasting
confidence: 77%
“…the relationship between energy losses as CH 4 and digestible DF obtained with results of Rijnen et al (2001) (n 4) is different from the relationship obtained with the results (n 25) of Shi (1993), Jørgensen et al (2001), Ramonet et al (2000) and Olesen et al (2001). The relationship obtained with these last four studies is close to the result of the present study with an increase of 1·3 kJ energy from CH 4 for each g additional digestible DF in the diet (Fig.…”
Section: Digestibility Of Dietary Fibre In Adult Sowsmentioning
confidence: 60%
See 1 more Smart Citation
“…However, Kirchgessner et al (1994) did not find any limitation in the fermentative capacity when feeding dry sows with graded level of alfalfa meal or wheat bran corresponding to the amount of dietary fibre fed in the present experiment. On the other side, doubling the amount of feed to pregnant sows in the last part of the pregnancy reduced the proportion of methane (CH 4 ) relative to the intake of metabolizable energy (ME) indicating that there is a limitation in the fermentative capacity of adult sows (Olesen et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 -exhalation by pigs is function of energy metabolism and can be derived from the heat production and the respiratory quotient (RQ, the ratio between the CO 2 production and O 2 consumption during respiration (Pedersen et al, 2008). For gestating sows, CO 2 production at animal level is estimated at 0.165 m 3 /h per 1000 W of total heat production, related to a RQ value of about 0.95 (Olesen et al, 2001;Rijnen et al, 2001;Theil et al, 2002). According to the CIGR equations (CIGR, 2002), it corresponds to an exhalation of about 2.6 kg CO 2 /day for the sows of the current essay.…”
Section: Discussionmentioning
confidence: 88%